A FSH-secreting pituitary adenoma discovered after ovarian hyperstimulation syndrome: a case report, illustrating pitfalls in the interpretation of serum FSH levels - Keigo Yano; Go Nakai; Hiroki Matsutani; Takashi Yamada; Masahide Ohmichi; Kazuhiro Yamamoto; Keigo Osuga (BMC Women's Health)
Abstract Background Most cases of ovarian hyperstimulation syndrome (OHSS) are caused by infertility treatment using human menopausal gonadotropin (HMG) and human chorionic gonadotropin (hCG). OHSS is widely known to have a “spoke-wheel” appearance on imaging, presenting as bilateral symmetric enlargement of ovaries with multiple cysts of varying sizes. When this spoke-wheel appearance is observed in patients not undergoing infertility treatment, tumor-derived hormones such as follicle-stimulating hormone (FSH) and hCG should be measured. However, pitfalls exist in the interpretation of FSH levels. Case presentation A 29-year-old, gravida 0, para 0 woman visited her local doctor for irregular menstruation and to seek fertility treatment. At the first medical examination, bilateral ovarian tumors were found by ultrasonography, and she was referred to our hospital. Magnetic resonance imaging (MRI) findings of the bilateral ovarian tumors suggested typical OHSS, and thus levels of serum hormones including FSH and hCG were measured to determine whether endogenous follicle-stimulating hormones were the cause. Estradiol was elevated at 737 pg/ml (normal: 28.8-196.8 pg/ml in follicular phase) and luteinizing hormone (LH) was low at < 0.3 mIU/ml (normal: 1.4–15 in follicular phase, 2.1–88 mIU/ml in ovulatory phase). FSH (18.6 mIU/ml; normal: 3.0-14.7 in follicular phase, 4.5–22.5 mIU/ ml) and hCG (< 1.0 mIU/ml) were within normal ranges for non-pregnant women. Initially, since ovarian neoplasms producing estrogen were suspected, surgical resection was scheduled. However, computed tomography of the neck to pelvic region was performed to rule out metastatic ovarian tumors, and indicated a coincidental pituitary lesion, which was pathologically characterized as an FSH-secreting pituitary adenoma. Consequently, the final diagnosis was OHSS caused by an FSH-producing pituitary adenoma and the scheduled ovarian surgery was avoided. Conclusions Awareness of MRI findings of OHSS is important to avoid unnecessary invasive procedures. When treating patients who have suspected OHSS on imaging but whose serum FSH is in the normal range, it is also important to know that an unsuppressed FSH level despite the negative feedback effect of high estrogen should prompt investigation for a pituitary adenoma as a primary consideration.